Pengembangan Keterampilan Pertunjukan Madihin Di Komunitas Madihinesia Kalimantan Selatan - Muhammad Budi Zakia Sani (Universitas Lambung Mangkurat, 2022)
Madihin art is an art that has a very strong local wisdom value. This art is played by individuals, in pairs, or in groups by madihin players called pamadihinan. Madihin art continues to grow in the wider community, its fans are emerging from the younger generation from various backgrounds and elements. They were gathered in a community which they named Madihinesia. This Madhinesian community was attended by dozens of members who were active and engaged in art activities in South Kalimantan. This community built a movement that aims to preserve and develop madihin art in South Kalimantan. Therefore, in this service activity, training is carried out aimed at developing the potential and skills possessed by the pamadihinan in the Madisonian community, so that it is a very big hope that they will be able to have increased skills in the future